Potential of NMR relaxometry to unravel the properties of mucilage in several pore sizes - Brax, Mathilde; Köhne, Maximilian; Kroener, Eva; Schaumann, Gabriele Ellen (Geoderma, 2019)
Soil-born exudates such as mucilage are known to affect soil physicochemical properties. Characterization of the gel properties of mucilage at the pore-scale is necessary to gain mechanistic understanding of the underlying processes leading to changes of soil properties. Yet, mucilage intrinsic properties' complicate its in-situ detection. Longitudinal and transverse magnetic relaxation rates measured with 1H Nuclear Magnetic Resonance (NMR) relaxometry have the potential to study mucilage-water interactions in-situ as they are sensitive to restricted molecular motion of water protons in biohydrogels. However, the relations between water mobility and biohydrogel properties in porous media have remained unknown until now. In this study, the mobility of water molecules in chia seed mucilage in porous systems was systematically investigated by means of 1H NMR relaxometry. Chia seed mucilage was used as it has hydrogel properties shared by a range of biological hydrogels found in soil. Glass beads of several sizes were used to study the influence of the pore size on the NMR signal. A conceptual model based on the equations describing the relaxation of water protons in porous media was developed to integrate these gel effects into the NMR parameters. The increased rigidity of the polymer network and its organization in the pore space, which depended on the particle size and the mucilage concentration, were assessed as the gel effects significantly affecting the bulk relaxation. Our approach, which combines the use of NMR along with other imaging methods, is a promising strategy to detect and characterize the properties of biohydrogel in porous media. •1H NMR relaxometry can characterize quantitatively mucilage in model soils.•Effect of mucilage on water mobility in model soils depends on particle size.•Several gel effects affect water mobility in mucilage-treated model soils.•Spider-web effect attests additional rigidity of the polymer network in the pore space.